Implementation of a triage nurse role and the effect on hospitalist workload. Issue 5 (20th October 2021) - Astik, Gopi J.; Kulkarni, Nita; Cyrus, Rachel M.; Yeh, Chen; O'Leary, Kevin J.
ABSTRACT: Objectives: Hospital medicine groups vary staffing models to match available workforce with expected patient volumes and acuity. Larger groups often assign a single hospitalist to triage pager duty which can be burdensome due to frequent interruptions and multitasking. We introduced a new role, the Triage nurse, to hold the triage pager and distribute patients. We sought to determine the effect of this Triage Nurse on the perceived workload of hospitalists and frequency of pages. Methods: We partnered with our patient throughput department to implement the Triage Nurse role who took the responsibility of tracking and distributing admissions among three admitting physicians along with coordinating report. We used the National Aeronautics and Space Administration-Task Load Index (NASA-TLX) to measure perceived workload and accessed pager logs of admitters for 3 months before and after implementation. Results: Overall, 50 of an expected 67 NASA-TLX surveys (74.6%) were returned in the pre-intervention period and 64 of 92 (69.6%) were returned in the post-intervention period. We found a statistically significant reduction in the domains of physical demand, temporal demand, effort and frustration from pre- to post-intervention periods (p < 0.01). There was also a significant decrease in the performance domain (p = 0.01) with a lower number indicative of better perceived performance. There was a significant reduction in the mean number of pages received by admitting hospitalists over their 9-h shifts (81.3 + 17.3 vs 52.4 + 7.3; p < 0.01). Conclusion: The implementation of the Triage Nurse role was associated with a significant decrease in the perceived workload of admitting hospitalists. Our findings are important because workload and interruptions can contribute to errors and burnout. Future studies should test interventions to improve hospitalist workload and evaluate their effect on patient outcomes and physician wellness.